2022
DOI: 10.1111/exd.14611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of itch and pain induced by bovine adrenal medulla (BAM)8–22, a new human model of non‐histaminergic itch

Abstract: Chronic itch is a socioeconomic burden with limited management options. Non‐histaminergic itch, involved in problematic pathological itch conditions, is transmitted by a subgroup of polymodal C‐fibres. Cowhage is traditionally used for studying experimentally induced non‐histaminergic itch in humans but encounters some limitations. The present study, therefore, aims to design a new human, experimental model of non‐histaminergic itch based on the application of bovine adrenal medulla (BAM)8–22, an endogenous pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Superficial blood perfusion was significantly enhanced when skin temperature was increased by 7°C for serotoninergic itch, while for cowhage-evoked itch it was increased both at +4 and +7°C above the resting skin temperature. This line of evidence confirm, what previously observed, that neurogenic inflammation is not necessary for the development of itch sensation because the first was increased exactly when the latter was not different from the control condition 49,80,92,189,190 . A very captivating explanation could be that increased superficial blood perfusion leads to increased tissue clearance and therefore this would counteract what would be an increased itch intensity, but this study does not provide enough data to make such an assumption.…”
Section: Enhanced Superficial Blood Perfusion Due To Innocuous Skin H...supporting
confidence: 91%
See 1 more Smart Citation
“…Superficial blood perfusion was significantly enhanced when skin temperature was increased by 7°C for serotoninergic itch, while for cowhage-evoked itch it was increased both at +4 and +7°C above the resting skin temperature. This line of evidence confirm, what previously observed, that neurogenic inflammation is not necessary for the development of itch sensation because the first was increased exactly when the latter was not different from the control condition 49,80,92,189,190 . A very captivating explanation could be that increased superficial blood perfusion leads to increased tissue clearance and therefore this would counteract what would be an increased itch intensity, but this study does not provide enough data to make such an assumption.…”
Section: Enhanced Superficial Blood Perfusion Due To Innocuous Skin H...supporting
confidence: 91%
“…Other itch models rely on the application of various pruritogens. Bovine adrenal medulla 8-22 (BAM8-22) can be applied to the skin to evoke an itch sensation similar to the one achieved with cowhage spicules 52,[90][91][92] . BAM8-22 is a direct agonist of MRGPRX1 and can be introduced by the use of intradermal injection or inactivated cowhage spicules soaked in a solution of this compound 90 .…”
Section: Itch Human Modelsmentioning
confidence: 99%
“…This may reflect the spatial contrast between strongly-activated fibers and non-activated fibers innervating the same site, causing a mismatched signal that is interpreted centrally as an itch [ 41 ]. Also previous studies of other groups showed that application of BAM 8-22 via spicules caused more itch then pain [ 42 , 43 ]. Another less focal application via 25 pricks evoked more pain and less itch [ 43 ].…”
Section: Discussionmentioning
confidence: 90%
“…Thus, antihistamines are frequently used for the treatment of itch in the clinic. The Mrgprs family, as the well-characterized histamine-independent itch receptors, can be activated by many endogenous and exogenous pruritogens, such as chloroquine, substance P and bovine adrenal medulla (BAM) 8-22 (Klein et al, 2021;Aliotta et al, 2022). Notably, the majority of chronic itches are insensitive to antihistamine treatment, thus suggesting the existence of histamine-independent mechanisms and distinct pruritogens that have yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%